196k views
3 votes
(X^25)^-6/(x-^3)^48 simplify

(X^25)^-6/(x-^3)^48 simplify-example-1
User Felix Ogg
by
5.3k points

2 Answers

4 votes

Answer:


x^(-6)

Explanation:

using the rules of exponents


(a^m)^(n) =
a^(mn)


(a^(m) )/(a^(n) ) =
a^(m-n)

simplifying numerator/ denominator


(x^(25(-6)) )/(x^(-3(48)) )

=
(x^(-150) )/(x^(-144) )

=
x^(-150-(-144))

=
x^(-150+144) =
x^(-6)



User Mantas Astra
by
5.2k points
5 votes


\frac{1}{ {x}^(6) }
hope this is what you are looking for
User Samer Murad
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.